(untitled) (Current Problems in Rail Vehicles, 2021)
Flange lubrication is a tool of friction modification at the wheel–rail interface, with the purpose of reducing wear and noise occurring at the contact of the flange with the rail head side. Possible solutions include solid lubricants – lubrication sticks pressed on the wheels of rail vehicles. For comparative testing of performance of solid lubricants, the European standard EN 16028 prescribes, albeit quite loosely, a method that employs a twin-disc test machine. In these tests, the wheel–rail contact pair is represented by two steel discs rolling on each other with constant creepage, and a specimen of the lubricant is applied and removed in a defined way. The paper gives an overview of the current state and presents the experience and findings of experimental activities that took place at the Faculty of Transport Engineering in recent years, including commercial research tasks carried out for suppliers and manufacturers of solid lubricants.